2020
DOI: 10.1177/1362361320926061
|View full text |Cite
|
Sign up to set email alerts
|

Atypical visual-auditory predictive coding in autism spectrum disorder: Electrophysiological evidence from stimulus omissions

Abstract: Autism spectrum disorder is a pervasive neurodevelopmental disorder that has been linked to a range of perceptual processing alterations, including hypo- and hyperresponsiveness to sensory stimulation. A recently proposed theory that attempts to account for these symptoms, states that autistic individuals have a decreased ability to anticipate upcoming sensory stimulation due to overly precise internal prediction models. Here, we tested this hypothesis by comparing the electrophysiological markers of predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
(71 reference statements)
4
13
1
Order By: Relevance
“…Given the latter, the higher amplitude omission responses in children could be explained as a consequence of a still imprecise predictive model, where high weight is assigned to sensory input in order to update the model. A similar interpretation of the oN1 has recently been proposed by van Laarhoven et al (2020) in the context of autism, where people suffering from autism demonstrated to assign a uniform, inflexibly high weight to prediction errors ( Van de Cruys et al, 2014 ). However, whether this hypothesis can be transferred to sensory predictions in children has to be addressed in future studies.…”
Section: Discussionsupporting
confidence: 57%
“…Given the latter, the higher amplitude omission responses in children could be explained as a consequence of a still imprecise predictive model, where high weight is assigned to sensory input in order to update the model. A similar interpretation of the oN1 has recently been proposed by van Laarhoven et al (2020) in the context of autism, where people suffering from autism demonstrated to assign a uniform, inflexibly high weight to prediction errors ( Van de Cruys et al, 2014 ). However, whether this hypothesis can be transferred to sensory predictions in children has to be addressed in future studies.…”
Section: Discussionsupporting
confidence: 57%
“…Individuals with ASD appear to set the weight of the prior lower (and that of the sensory inputs higher) than optimal when the environment shifts from a normal to an unpredictable, volatile regimen. A similar inability to adapt to process unexpected sensory stimulation has been reported in several recent studies [4,24,36,51]. For example, using audiovisual recordings of hand-clapping with unexpected omissions of sound [51] found an early negative omission response (the oN1 component of the event-related potential) -a key signature of processing unexpected sensory stimulation -to be significantly more pronounced in their ASD relative to the TD group.…”
Section: Discussionsupporting
confidence: 79%
“…They found no differences in predictive gaze. van Laarhoven, Stekelenburg, Eussen, and Vroomen [2020] considered neural activity indicative of predictions based on the association between the sight and sound of a handclap. The ASD group showed increased modulation of neural activity by prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Both showed reduced modulation by prediction of the early ERP response to auditory stimuli in the ASD group compared to the control group. A third study examining the effect of auditory omission during an auditory visual action (i.e., hand clap) showed an increased oN1 in the ASD group compared to the NT group, suggesting a larger prediction error in the ASD group compared to the NT group [van Laarhoven et al, 2020].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation